Analysis of the need for interactive video learning media on sequences and series material - Intan Pramuditya Hartanti; Eko Andy Purnomo; Abdul Aziz (UNION : Jurnal Ilmiah Pendidikan Matematika, 2024)
The teaching methods employed at SMA Muhammadiyah 1 Semarang still predominantly use lecture-based approaches, and the use of instructional media remains suboptimal. Students' mathematical problem-solving abilities are relatively low, as evidenced by their continued difficulties in modeling word problems into mathematical forms. This study aims to analyze the need for digital learning media to improve students' mathematical problem-solving skills. Digital learning media allow students to access materials flexibly while also providing interactive tools designed to enhance problem-solving skills, particularly in understanding complex mathematical concepts such as sequences and series. The research method is descriptive qualitative, with the research instrument being a questionnaire using a 1-4 Likert scale. The questionnaire was distributed via Google Forms to 69 tenth-grade students at SMA Muhammadiyah Semarang, located in Semarang City, Central Java. After completing the questionnaire, in-depth interviews were conducted with students to support the collected data. A descriptive qualitative method was chosen because this approach enables researchers to explore students' needs and perceptions regarding the use of digital learning media more deeply. The findings indicate a lack of effective use of instructional media (an average score of 1.95 out of 4), significant challenges in problem-solving (an average score of 2.61 out of 4), and difficulties in understanding the material on sequences and series (an average score of 2.57 out of 4). The results of the study underscore the need for the development of digital learning media to address students' difficulties in understanding sequences and series, as well as to enhance their problem-solving skills. Digital learning media provide interactive materials and exercises specifically designed for the topic of sequences and series, which can be implemented at SMA Muhammadiyah 1 Semarang, where students can access materials and practice problems via mobile phones during lessons or as homework to support independent learning.